Study on the Control Strategy of Engine Brake of Vehicle with New Type Multi Pieces Metal Belt Drive - Song Limin (Jixie chuandong)
For the long process of automobile engine braking capacity and speed brake assist stability poor problems,by introducing multi pieces metal belt drive into vehicle transmission system,the numerical model of a new type multi pieces metal belt vehicle transmission system is established,under the long downhill course conditions,the multi pieces metal belt drive engine brake control strategy,its feasibility and the influence law on braking characteristic are studied.